Cell interactions and osteogenic differentiation on marine sponge-derived scaffolds: a systematic review - Jonas de Araújo Silva; Adriel Filipe Santos Braga da Silva; Amanda Sardeli Alqualo; Beatriz Viegas; Ana Cláudia Muniz Rennó; Renata Neves Granito (Biofunctional Materials)
Marine sponges, with their unique blend of organic and inorganic components, hold promise as biomaterials for bone tissue engineering. In this study, we systematically reviewed and comprehensively analysed in vitro assays evaluating osteogenic cell behaviour on scaffolds derived from marine sponges. Additionally, we investigated the potential of these scaffolds to induce cell differentiation and viability. Our analysis included 2,291 publications, with nine studies meeting the eligibility criteria for qualitative analysis. Results consistently showed strong adhesion of osteogenic cells to marine sponge-derived scaffolds facilitated by the interconnected porous structure. Cells exhibited elongated morphologies along scaffold fibres, indicative of a favourable growth environment. Comparative analyses demonstrated superior cell adhesion on marine sponge-derived scaffolds compared to other materials. Cell proliferation was observed across all studies, with a notable increase throughout the culture period. Marine sponge-derived scaffolds induced osteogenic differentiation, evidenced by osteocalcin and osteopontin expression. Notably, differences in cellular differentiation were attributed to diverse scaffold manufacturing methods. Our study highlighted the lack of standardised test procedures and the moderate risk of bias in the analysed studies, emphasising the need for further research with established protocols. Overall, this comprehensive analysis sheds light on osteogenic cell interactions with marine sponge-derived scaffolds, positioning them as promising biomaterials for bone tissue engineering. Understanding cellular responses to these scaffolds opens new possibilities for advanced research and regenerative medicine applications.